Sodium Houttuyfonate Alleviates Post-infarct Remodeling in Rats via AMP-Activated Protein Kinase Pathway - Zheng, Cheng; Lin, Jia-Feng; Lin, Zhong-Hao; Lin, Wei-Qian; Thapa, Saroj; Lin, Yuan-Zheng; Lian, Hao; Liu, Zhi-Rui; Chen, Jia-Hui; Li, Xiao-Wei (Frontiers in Pharmacology, 2018)
With the chronic ischemia persisting after acute myocardial infarction, the accompanying low-degree inflammation and subsequent fibrosis result in progression of cardiac remodeling and heart failure. Recently, Sodium Houttuyfonate (SH), a pure compound extracted from Houttuynia Cordata, has been confirmed exerting anti-inflammatory and anti-fibrotic effects under diseased situations. Here, we aimed to investigate whether SH could reverse the cardiac remodeling post-myocardial infarction by alleviating cardiac inflammation and fibrosis. Left anterior descending coronary artery of adult male Sprague-Dawley rats was ligated to elicit myocardial infarction. Low and high dose of SH was administered by oral gavage for 4 consecutive weeks post myocardial infarction. Long-term SH treatment decreased heart rate, heart weight/ body weight (HW/BW) and left ventricle weight/ body weight (LVW/BW), reduced cardiac expression of brain natriuretic peptide (BNP), improved left ventricular heart function, and ameliorated the histopathological changes caused by myocardial infarction. Western blotting revealed the expression of tumor necrosis factor–α (TNF-α), interleukin-6 (IL-6), transforming growth factor-β (TGF-β), collagen I, and collagen III of the infarcted ventricle were reduced by SH treatment. Meanwhile, we found that SH treatment post-myocardial infarction activated AMP-activated protein kinase (AMPK) and suppressed nuclear factor-κB p65 (NF-κB p65). Furthermore, on H9C2 cells induced hypoxic injury with cobalt chloride (CoCl2), the reduction of inflammatory cytokines (IL-6, TNF-α, and TGF-β), activation of AMPK, and suppression of NF-κB p65 were also observed by SH treatment. However, transfection of H9C2 with AMPKα siRNA blunted the suppression of NF-κB p65 and inflammatory cytokines (IL-6, TNF-α, and TGF-β) by SH post-hypoxia. Taken together, these findings suggested that long-term administration of SH post myocardial infarction reduced cardiac inflammatory and fibrotic responses, and reversed cardiac remodeling process. The underlying mechanism may be activating AMPK and suppressing NF-κB pathway.